Chyme reinfusion therapy using new technology - Gil Hardy (World Nutrition Journal, 2023)
High output double enterostomies (DES) and disease-related malnutrition (DRM) are features of intestinal failure (IF) that require parenteral nutrition (PN) until surgical re-establishment of intestinal continuity. PN risks include gut and hepatobiliary dysfunction and Intestinal failure associated liver disease (IFALD), defined as hepatobiliary dysfunction with elevated liver function tests (LFT). Chyme reinfusion therapy (CRT) is a distal feeding technique recommended for restoration of digestive function.